2011
DOI: 10.1007/s10600-011-9872-x
|View full text |Cite
|
Sign up to set email alerts
|

Phenylpropanoids and polysaccharides from Plantago depressa and P. media growing in Buryatia

Abstract: The composition of phenylpropanoids and polysaccharides from leaves of Plantago depressa and P. media (Plantaginaceae) growing in Buryatia was studied. Caffeic and chlorogenic acids and acteoside were found in the studied plants; isoacteoside and plantamajoside, in P. media. The dominant compound in P. depressa was acteoside (8.72 mg/g); in P. media, plantamajoside (7.69 mg/g). These were responsible for the pronounced antiradical activity. Polysaccharide components that were extracted by water and an oxalate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 17 publications
(12 reference statements)
0
22
0
Order By: Relevance
“…Similar results have been reported by Kardošová [25], who determined arabinose (26.0%) as a predominant neutral monosaccharide in water-extractable polysaccharides from P. lanceolata leaves, while Samuelsen et al [26] reported almost equal levels of arabinose (8.8-24%), galactose (8-34%), and xylose (11-22%) in polysaccharide fractions from P. major leaves. Olennikov et al [27] determined a high content of galacturonic acid in water-extractable polysaccharides from P. media leaves (41.9-61.0%), confirming the presence of pectin-type polysaccharides, as well as galactose (15.6 and 13.6%) and arabinose (6.7 and 9.4%), suggesting the presence of arabinogalactans as side chains.…”
Section: Sugar Compositionmentioning
confidence: 94%
“…Similar results have been reported by Kardošová [25], who determined arabinose (26.0%) as a predominant neutral monosaccharide in water-extractable polysaccharides from P. lanceolata leaves, while Samuelsen et al [26] reported almost equal levels of arabinose (8.8-24%), galactose (8-34%), and xylose (11-22%) in polysaccharide fractions from P. major leaves. Olennikov et al [27] determined a high content of galacturonic acid in water-extractable polysaccharides from P. media leaves (41.9-61.0%), confirming the presence of pectin-type polysaccharides, as well as galactose (15.6 and 13.6%) and arabinose (6.7 and 9.4%), suggesting the presence of arabinogalactans as side chains.…”
Section: Sugar Compositionmentioning
confidence: 94%
“…However, other scientists had found that younger leaves of P. major contained a higher concentration of plantamajoside than older leaves (Zubair et al, 2011). The leaves of Plantago media, P. major, P. lanceolata, Plantago depressa and P. asiatica were analyzed in several studies (Budzianowska et al, 2004;Zubair et al, 2011Zubair et al, , 2012aOlennikov et al, 2011;Gonda et al, 2013;Li et al, 2008). The highest content was found in P. major leaves with 12.43 mg g À1 DW (Zubair et al, 2012a,b).…”
Section: Plantamajoside In Different Plant Parts and In Vitro Culturesmentioning
confidence: 99%
“…The aerial parts of Plantago media L., P. major, P. lanceolata L., Plantago depressa (Willd.) and P. asiatica have been analyzed for the content of plantamajoside and verbascoside (Olennikov et al, 2011;Gonda et al, 2013). Bioactive plant components are well known from many plant species (Byamukama et al, 2015;Ogwuche et al, 2015;Adagba et al, 2017;Sawadogo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%